HUBUNGAN PENDIDIK, PESERTA DIDIK, DAN MASYARAKAT: ANALISIS SOSIAL PEMBENTUKAN KARAKTER GENERASI MUDA - Fitriasari Fitriasari; Muh. Asril; Alya Devika; Samsinar Syarifuddin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The rapid flow of digital transformation, which has triggered the phenomenon of social dysfunction in the form of a decline in public communication ethics and the degradation of the morality of the younger generation, is the background to this scientific study. These macro issues demand integrated collaborative governance to fortify adolescent personalities from the negative impacts of cyber modernity. The main focus of this research is a sociological analysis of the triad relationship between the role of educators, the existence of students, and societal structures in character formation. The research steps were carried out using a qualitative approach with a library research method for the period 2020-2026. The actual data collection procedure was collected through the study of curriculum document texts and the processing of relevant secondary literature, which was then executed through content analysis techniques including data reduction, logical presentation, and drawing sociological conclusions. Theoretical findings reveal that the non-formal community environment acts as an active sociological space as well as a real laboratory that dictates students' emotional and spiritual maturity. Community social supervision (social control) significantly strengthens the function of traditional controls in reducing deviant behavior. The main conclusion confirms that the synergistic integration between the three educational centers successfully realizes the formation of a balanced and responsive human character responsive to the challenges of the times. Educators are recommended to design dialogical-contextual guidance strategies that consistently involve local religious figures. ABSTRAK Derasnya arus transformasi digital yang memicu fenomena disfungsi sosial berupa penurunan etika komunikasi publik serta degradasi moralitas generasi muda melatarbelakangi kajian ilmiah ini. Masalah makro tersebut menuntut adanya tata kelola kolaboratif terintegrasi guna membentengi kepribadian remaja dari dampak negatif modernitas siber. Fokus utama penelitian ini adalah menganalisis secara sosiologis hubungan triad antara peran pendidik, eksistensi peserta didik, dan struktur masyarakat dalam pembentukan karakter. Langkah-langkah penelitian dijalankan menggunakan pendekatan kualitatif dengan metode studi kepustakaan (library research) periode 2020-2026. Prosedur pengumpulan data aktual dihimpun lewat studi teks dokumen kurikulum serta pengolahan literatur sekunder yang relevan, yang selanjutnya dieksekusi melalui teknik analisis isi (content analysis) meliputi reduksi data, penyajian logis, dan penarikan kesimpulan sosiologis. Temuan teoretis menyingkap bahwa lingkungan nonformal masyarakat bertindak sebagai ruang sosiologis aktif sekaligus laboratorium rill yang mendikte kematangan emosional dan spiritual siswa. Pengawasan sosial (social control) komunitas secara signifikan memperkuat fungsi kontrol tradisional dalam mereduksi perilaku menyimpang. Simpulan utama menegaskan bahwa integrasi sinergis antartiga pusat pendidikan sukses merealisasikan pembentukan karakter insan kamil yang seimbang dan responsif terhadap tantangan zaman. Pendidik direkomendasikan merancang strategi bimbingan dialogis-kontekstual yang melibatkan tokoh agama lokal secara konsisten.